Electronic Government For The Digital Divide’s reduction - Issa Fontalvo, Sugey Martha (Ingeniería Solidaria, 2011)
The author explains the concept of electronic government from the social and governmental perspectives. He also describes how the internet can encourage the participation of more people in social development. Throughout the text he discusses how the New Information and Communications Technologies (nict) have prompted major changes in society and have created at the same time a barrier between people who use them, and those who haven’t incorporated those into their daily life; this barrier is the digital divide. He comments about the need of implementing government strategies that aim to bring nicts to all the nucleus of society in order to reduce the digital divide between those who manage the nicts and those who don’t have access to them. The author also meditates on the need to promote digital literacy, so all citizens can participate of the resources of the Internet.